Characterization of films based on enzymatically modified chitosan derivatives with phenol compounds. (October 2016) - Aljawish, Abdulhadi; Muniglia, Lionel; Klouj, Amira; Jasniewski, Jordane; Scher, Joël; Desobry, Stephane
Abstract: Enzymatic modification of chitosan particles by the ferulic acid (FA) and ethyl ferulate (EF) oxidation products using Myceliophtora thermophyla laccase in mild conditions (pH 7.5, 30 °C in aqueous medium) was investigated. The chitosan derivatives showed an increase of degree of acetylation (DA), molecular mass (MM) and viscosity in comparison with chitosan. Chitosan and its derivatives films were characterized in terms of physicochemical, surface, barrier, mechanical and antioxidant properties. The results showed that the chitosan derivative films were colored (yellow-orange) for FA and colorless for EF compared to colorless chitosan films. The oxidation products grafted onto chitosan increased the dry matter content, thickness and heterogeneous surface of chitosan derivative films. Owing to the hydrophobic character of oxidation products, chitosan derivative films showed a low capacity of moisture capture and sorption at different levels of relative humidity (RH). Low moisture content improved the barrier properties and decreased the mechanical properties of chitosan derivative films. Furthermore, the presence of phenol products onto chitosan improved the antioxidant properties of its derivative films. Despite the phenol content of FA-chitosan films was higher than that of EF-chitosan films; no significant change was noticed in thickness, water sorption isotherms as well as barrier and mechanical properties. Interestingly, FA-chitosan films showed higher antioxidant properties in comparison with EF-chitosan films. It could be concluded that the enzymatic grafting of phenol compounds onto chitosan is a promising process to create useful functional materials for industrial applications such as food packaging. Graphical abstract: Highlights: Films of chitosan and its enzymatically modified derivatives were manufactured. Chitosan derivative films were colored for ferulic acid and colorless for ethyl ferulate. Phenol grafting increased thickness and topography surface of chitosan derivative films. Water sorption and mechanical properties of chitosan derivative films were decreased. Chitosan derivative films showed improved antioxidant and barrier properties.